2004
DOI: 10.1007/s10286-004-0220-0
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hypotension treated with acarbose in a patient with type 1 diabetes mellitus

Abstract: Treatment of postprandial hypotension (PPH) is often unsuccessful. We report a case of a type 1 diabetic patient suffering from severely symptomatic PPH. The patient was treated with acarbose and showed definite improvement of both glycemic control and PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The glycemic responses to intraduodenal glucose were comparable in studies with and without gastric distension (8). Furthermore, insulin is unlikely to play a major role in postprandial hypotension, since intravenous glucose has little, if any, effect on blood pressure, and postprandial hypotension occurs in type 1 diabetic patients (23,25), who are, by definition, insulin-deficient. The observed effects of gastric distension on the stimulation of SMA blood flow are of considerable interest, particularly given the paucity of previous information.…”
Section: Discussionmentioning
confidence: 89%
“…The glycemic responses to intraduodenal glucose were comparable in studies with and without gastric distension (8). Furthermore, insulin is unlikely to play a major role in postprandial hypotension, since intravenous glucose has little, if any, effect on blood pressure, and postprandial hypotension occurs in type 1 diabetic patients (23,25), who are, by definition, insulin-deficient. The observed effects of gastric distension on the stimulation of SMA blood flow are of considerable interest, particularly given the paucity of previous information.…”
Section: Discussionmentioning
confidence: 89%
“…This was, however, important to exclude, as hyperglycemia (2,26), including variations in blood glucose that are within the normal postprandial range (1,37), affects gastric motility. While elevations in blood glucose and insulin appear unlikely to play a major role in postprandial hypotension, since intravenous glucose has little, if any, effect on blood pressure and postprandial hypotension occurs in type 1 diabetic patients, who are, by definition, insulin-deficient (27,28), this does not discount the relevance of potential hormonal factors. An increase in sympathetic activity may potentially account for the effects of gastric distension, particularly as gastric distension has been shown to increase muscle sympathetic nerve activity in healthy young and older subjects, although the magnitude of the increase was less in the elderly (44).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous observations that patients with type 1 diabetes mellitus who, by definition, are insulin deficient, also develop PPH. 24 The action of acarbose on glucose absorption affects a common pathway that influences the secretion of other gut hormones with known vasodilatory actions, such as neurotensin. 26,41 It is likely that more than one vasodilator is involved in the pathophysiology of PPH.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports found improvement of PPH in patients with type 1 24 and type 2 25 diabetes mellitus. Furthermore, Maruta et al 26 showed that voglibose, another ␣-glucosidase inhibitor, also attenuates PPH in patients with neurologic disorders, such as multiple system atrophy and Parkinson disease.…”
mentioning
confidence: 99%